2008
DOI: 10.1111/j.1538-7836.2007.02843.x
|View full text |Cite
|
Sign up to set email alerts
|

Three novel β3 domain-deletion peptides for the sensitive and specific detection of HPA-4 and six low frequency β3-HPA antibodies

Abstract: Immunologic and structural analysis of eight novel domain-deletion b 3 integrin peptides designed for detection of HPA-1 antibodies. This issue, pp 366-75.Summary. Background: Antibodies against human platelet antigens (HPA) are clinically important in fetal-maternal alloimmune thrombocytopenia, refractoriness to platelet transfusions and post-transfusion purpura. Of the 16 HPAs, nine are located on the b3 subunit of the aIIbb3 integrin. Antibody detection is generally based on platelet-derived aIIbb3 from HPA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 30 publications
0
20
0
Order By: Relevance
“…23,30 In this respect, the use of recombinant PLT alloantigens may help in the further development of the SPR technique for the detection of PLT antibodies. 11,31 In conclusion, our results showed that the SPR method can facilitate the diagnosis of clinically relevant low-avidity HPA-1a antibodies. Further studies are required to establish the impact of this new method in determining the binding characteristics of maternal antibodies as predictive parameter for the clinical severity of NAIT.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…23,30 In this respect, the use of recombinant PLT alloantigens may help in the further development of the SPR technique for the detection of PLT antibodies. 11,31 In conclusion, our results showed that the SPR method can facilitate the diagnosis of clinically relevant low-avidity HPA-1a antibodies. Further studies are required to establish the impact of this new method in determining the binding characteristics of maternal antibodies as predictive parameter for the clinical severity of NAIT.…”
Section: Discussionmentioning
confidence: 56%
“…The question as to whether this technique is also applicable to other human PLT antigens, especially for “labile” HPAs (HPA‐2, ‐3, and ‐15), remains 23,30 . In this respect, the use of recombinant PLT alloantigens may help in the further development of the SPR technique for the detection of PLT antibodies 11,31 …”
Section: Discussionmentioning
confidence: 99%
“…Given that panel cells carrying low frequency HPA antigens are not readily available, sequencing of relevant exons encoding known low frequency HPA antigens in paternal DNA may be required to identify the probable sensitizing antigen. Transfected cell lines expressing low frequency antigens (Kroll et al , ) or recombinant glycoprotein fragments engineered to carry relevant epitopes (Stafford et al , ,b) that can be used to identify such antibodies may become available in the future. Although many low frequency antigens have been described (Table ), sensitization to these markers probably accounts for no more than a few percent of all cases of NAIT (Ghevaert et al , ).…”
Section: Laboratory Diagnosis Of Naitmentioning
confidence: 99%
“…In addition, we have demonstrated in other proof-ofprinciple studies that recombinant proteins can be used for the detection of alloantibodies against HPA-2, 30 HPA-4, 31 HPA-5, and HPA-15 32 and several of the extremely low-frequency HPAs on the b3 integrin. 31,33 With the addition of other recombinant HPAs, the Luminex multiplex technique would be extremely useful in enabling the prompt diagnosis and management of alloimmune PLT disorders. Furthermore, large-scale screening for HPA antibodies becomes feasible with an affordable and simple-touse bead assay as described here.…”
Section: Discussionmentioning
confidence: 99%